Sosialisasi Keaksaraan Fungsional untuk Lembaga Keagamaan - Nani Nur’aeni; Ikka Kartika A. Fauzi; Gatot Yusuf Effendi (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2011)
Literacy education is quite fundamental to building up human quality with dignity both socially and economically. Socially, individual will gain appreciation from society and  it provides opportunities to achieve their welfare economically. Considering unfinished illiteracy in Indonesia, so the acceleration of illiteracy eradication is becoming a necessary part that should be supported by all society components. Similarly, prevailance of religious institutions is highly effective to develop educational literacy institution. In addition, having values and norms system binding the community, as well as religious institutions quantitatively can reach all levels of society. To strengthen the effectiveness implementation program, it is necessary to socialize literacy education that provides an illustration both of educational and implementation model so that  the optimalization target achievement in education could be gained optimally.